Students’ Challenges In Academic Writing: A Phenomenological Study - Annisa Rifka Kirana; Dodi Siraj Muamar Zain (Proceedings Series on Social Sciences & Humanities, 2026)
Academic writing is one of the main challenges faced by students, especially in the context of English as a foreign language. This study aims to explore the challenges students face in completing academic writing and the strategies they use to overcome these challenges. This research employed a qualitative method with a phenomenological approach. Data were collected through semi-structured interviews with students who were completing their academic writing. The findings show that students experienced several challenges, including difficulties in developing ideas and paragraphs, linguistic issues such as grammar and vocabulary, lack of motivation, difficulty finding relevant references, problems related to supervisors, difficulty determining research topics, and limited understanding of academic writing structure. To overcome these challenges, students used several strategies, including using AI tools, reading more academic references, discussing with supervisors, setting personal deadlines, and building self-motivation. These findings indicate that students need both internal strategies and external support to complete academic writing effectively. This study provides insights for students, lecturers, and institutions in supporting the academic writing process.